Characteristics of Cells from Five Exotic Bamboos after Drywood Termites Incisitermes minor (Hagen) Attack - Subekti, Niken; Yoshimura, Tsuyoshi (Biosaintifika: Journal of Biology & Biology Education, 2015)
This study examined the relationship between and the characteristics of five bamboos exotic in the cell walls. For this purpose, the bamboosexotic from Indonesia were separated into cells after drywood termites Incisitermes minor (Hagen) attack. SEM observations revealed that bamboos cells. Moreover, SEM analysis showed that the cellulose isolated from parenchyma cells. These results suggest that all the cellulose micro?brils in five bamboos different characteristics of cell function after drywood termite attack.Penelitian ini menguji hubungan antara karakteristik dan lima bambu eksotis di dinding sel. Untuk tujuan ini, bamboosexotic dari Indonesia dipisahkan ke dalam sel setelah rayap Drywood Incisitermes minor (Hagen) serangan. Pengamatan SEM menunjukkan bahwa sel-sel bambu. Selain itu, analisis SEM menunjukkan bahwa selulosa yang diisolasi dari sel parenkim. Hasil ini menunjukkan bahwa semua brils fi selulosa mikro di lima bambu karakteristik yang berbeda dari fungsi sel setelah serangan Rayap Kayu Kering.